2020
DOI: 10.13057/biodiv/d220132
|View full text |Cite
|
Sign up to set email alerts
|

Bird community structure as a function of habitat heterogeneity: A case of Mardi Himal, Central Nepal

Abstract: Abstract. Pandey N, Khanal L, Chapagain N, Singh KD, Bhattarai BP, Chalise MK. 2021. Bird community structure as a function of habitat heterogeneity: A case of Mardi Himal, Central Nepal. Biodiversitas 22: 262-271. Community structure of birds at different habitat types is underexplored in the montane environment of the central Himalaya. Therefore, this study explored bird community structure in different habitat types in Mardi Himal of the Annapurna Conservation Area, central Nepal, and tested association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…Number of fruiting trees present in the forest or agriculture or human settlement areas added more food availability for the herbivore birds. Hence, specific fruiting seasons increased the abundance of herbivore birds (Pandey et al 2021). The avian research conducted by Herzog et al (2005) in the Swiss agricultural landscape reported the pastureland didn't contribute to bird diversity but our study found that agriculture along with settlements and grassland supported higher omnivores and insectivore bird diversity.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Number of fruiting trees present in the forest or agriculture or human settlement areas added more food availability for the herbivore birds. Hence, specific fruiting seasons increased the abundance of herbivore birds (Pandey et al 2021). The avian research conducted by Herzog et al (2005) in the Swiss agricultural landscape reported the pastureland didn't contribute to bird diversity but our study found that agriculture along with settlements and grassland supported higher omnivores and insectivore bird diversity.…”
Section: Discussioncontrasting
confidence: 52%
“…The species discovery curve for Kahundanda clearly showed the sufficient sampling efforts for the birds. Similar type of species discovery curve was also used in the study of birds by La Sorte & Somveille (2020) and Pandey et al (2021). The relative species abundance is a major component of biodiversity and indicate how common and rare species are relative to other species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The birds were identified using binoculars and field guide book (Grimmett et al, 2016). Birds were categorized to their feeding guilds following Katuwal et al (2018) and Pandey et al (2021).…”
Section: Study Design and Bird Surveymentioning
confidence: 99%